Prebiotic potential of gum Arabic for gut health - Elnour, Ahmed Adam Hassan Mohammed; Abdurahman, Nour Hamid; Musa, Khalid Hamid; Rasheed, Zafar (Qassim University, 2023)
Gum Arabic (GA), or Gum Acacia, is a natural polysaccharide extensively employed as a food additive and stabilizer, deriving its origin from the exudates of Acacia trees.[1] Although traditionally prized for its emulsifying, thickening, and stabilizing attributes in the food and beverage industry,[2] research has highlighted GA’s potential health benefits, especially as a prebiotic in the human gut.[3,4] The human gut microbiome, an intricate ecosystem of trillions of microorganisms, including bacteria, fungi, and viruses, helps to preserve overall health.[5] A well-balanced, diverse microorganism community in the gut is essential,[6] as disturbances in the microbiome have been linked to several health complications, such as inflammatory bowel disease, obesity, and mental health disorders.[7,8] Thus, GA, traditionally a food ingredient, exhibits potential as a health-promoting prebiotic in the human gut.